The effect of FAAH, MAGL, and Dual FAAH/MAGL inhibition on inflammatory and colorectal distension‐induced visceral pain models in Rodents. Issue 7 (13th April 2015) - Sakin, Y. S.; Dogrul, A.; Ilkaya, F.; Seyrek, M.; Ulas, U. H.; Gulsen, M.; Bagci, S.
Abstract Background Recent studies showed that the pharmacological inhibition of endocannabinoid degrading enzymes such as fatty acid amide hydrolase (FAAH) and monoacyl glycerol lipase (MAGL) elicit promising analgesic effects in a variety of nociceptive models without serious side effects. However, the full spectrum of activities is not observed upon inhibition of either FAAH or MAGL enzymes alone and thus dual FAAH and MAGL inhibitors have been described. Visceral pain is strongly associated with inflammation and distension of the gut. Thus, we explored the comparable effects of FAAH, MAGL, and dual FAAH/MAGL inhibitors on inflammatory and mechanically evoked visceral pain models. Methods Visceral inflammatory and distension‐induced pain were assessed with the 0.6% acetic acid writhing test in mice and colorectal distension (CRD) test in rats, respectively. The selective FAAH inhibitor PF 3845, MAGL inhibitor JZL 184, dual inhibitor JZL 195, and the cannabis analog CP 55, 940 were given systemically 30 min prior to nociceptive testing. Key Results PF 3845 (5, 10, and 20 mg/kg), JZL 184 (5, 10, and 20 mg/kg), and JZL 195 (5, 10, and 20 mg/kg) elicit dose‐dependent antinociceptive in the acetic acid writhing test. In the CRD model, while JZL 195 (5, 10, or 20 mg/kg) and PF3845 (10, 20, and 40 mg/kg) produced dose‐dependent antinociceptive effects comparable to those of CP 55, 940 (0.1, 0.3, or 1 mg/kg), JZL 184 (10, 20, and 40 mg/kg) alone did not alter the visceromotor response (VMR). Conclusions & Inferences The selective FAAH inhibitor and dual FAAH/MAGL inhibitors were effective in both inflammatory and mechanically evoked visceral pain, while the MAGL inhibitor elicited an analgesic effect in inflammatory, but not in distension‐induced, visceral pain.